2021
DOI: 10.3233/jad-201186
|View full text |Cite
|
Sign up to set email alerts
|

Broader Insights into Understanding Tumor Necrosis Factor and Neurodegenerative Disease Pathogenesis Infer New Therapeutic Approaches

Abstract: Proinflammatory cytokines such as tumor necrosis factor (TNF), with its now appreciated key roles in neurophysiology as well as neuropathophysiology, are sufficiently well-documented to be useful tools for enquiry into the natural history of neurodegenerative diseases. We review the broader literature on TNF to rationalize why abruptly-acquired neurodegenerative states do not exhibit the remorseless clinical progression seen in those states with gradual onsets. We propose that the three typically non-worsening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 204 publications
0
15
0
Order By: Relevance
“…Andre et al considered anti-inflammatory properties of extracts from five apple cultivars, selected mainly for variation in polyphenol composition [14]. They compared their effects in two cell-based assays, targeting critical points in the inflammation pathway, namely nuclear factor kappa B (NF-κB) activation and expression of tumour necrosis factor alpha (TNFα), both implicated in the onset and progression of diseases associated with acute or chronic inflammation such as inflammatory bowel disease (IBD) [15] and neurodegenerative diseases [16]. They found that those with high levels of particular types of polyphenols targeted these two different, but important, parts of the inflammatory pathway in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Andre et al considered anti-inflammatory properties of extracts from five apple cultivars, selected mainly for variation in polyphenol composition [14]. They compared their effects in two cell-based assays, targeting critical points in the inflammation pathway, namely nuclear factor kappa B (NF-κB) activation and expression of tumour necrosis factor alpha (TNFα), both implicated in the onset and progression of diseases associated with acute or chronic inflammation such as inflammatory bowel disease (IBD) [15] and neurodegenerative diseases [16]. They found that those with high levels of particular types of polyphenols targeted these two different, but important, parts of the inflammatory pathway in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this result has been confirmed in neurodegenerative diseases such as Alzheimer’s and multiple sclerosis, characterized by serious cognitive disabilities. Under these conditions, the new neuroprotective pharmacological strategy is based on the inhibition of TNF-α, which, according to the results collected, seems to have a protective effect on patients with mild cognitive deterioration by counteracting inflammation [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke is a neurological disorder resulted from loss of blood supply leading to neuronal damage. Dead neurons generate danger-associated molecular patterns (DAMPs) triggering excessive inflammatory responses [ 13 , 14 ]. Microglia are the resident immune cells in the brain and play a central role in the postischemic inflammation.…”
Section: Discussionmentioning
confidence: 99%